Acute kidney injury with consumption of raw gall bladder of Indian carp fish (Labeo rohita): A single center study from India. Issue 1 (16th December 2018) - Krishna, Amresh; Singh, Prit P; Vardhan, Harsh; Kumar, Om; Prasad, Govind
ABSTRACT: Aim: This retrospective study examined the clinical presentation and outcome of all patients who presented with acute kidney injury (AKI) following consumption of uncooked fish gallbladder as folk medicine. Methods: We reviewed all cases admitted at our institute between 1 January 1997 and 31 December 2016 following ingestion of fish gallbladder (Indian carp/ Labeo rohita ). Results: A total 32 of patients were included, with a male: female ratio of 3:1 and mean age 44.34 ± 13.33 years. The mean number of gall bladder consumed was 4.59 ± 4.75. All 32 patients presented with hepatic and renal failure. The mean duration of onset of symptoms following ingestion was 6.47 ± 2.84 h. At the time of admission, urine output was 187.9 ± 141 mL/24 h, serum creatinine 11.66 ± 2.50 mg/dL, serum bilirubin 6.14 ± 3.91 mg/dL, serum glutamate‐pyruvate transaminase (SGPT) 687 ± 458 IU/L and serum glutamic oxaloacetic transaminase (SGOT) 188 ± 181 IU/L. All but one patient required haemodialysis. Twenty‐seven patients were discharged with recovering acute kidney injury while five patients died. Mean duration of hospital stay was 12.94 ± 8.31 days. Mean number of haemodialysis sessions received by patients was 4.59 ± 3.12. Interval between consumption and onset of symptoms, serum bilirubin and SGPT were found to be significantly different between those who survived and died. Conclusion: Acute kidney injury associated with ingestion of raw fish gallbladder is associated with significant morbidity and mortality. Summary at a Glance: This case series describes development of acute kidney injury following consumption of raw fish gall bladder, this series highlights the importance of careful history taking in eliciting unusual causes of AKI in rural Indian communities.